Evaluation of some optimal chemotherapy protocols by using a gradient method - Duda, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents some optimal problems resulting from cancer chemotherapy. Two bilinear models of a cell population cycle and a linear performance index are considered. A numerical gradient method is applied to solve the problems. Some properties and related simulation results of optimal control strategies are discussed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka